Infant with Congenital Anomalies: Born To Die? - Singh, S Bitam; Phanjoubam, Memchoubi; Devi , Th Meera (Journal of Indian Academy of Forensic Medicine, 2015)
Forensic investigation of foetuses, stillbirths and new-borns and their differential diagnosis often present many difficulties. In practice all cases of abandoned new-borns deaths are reported to the police, who ask for a post-mortem examination because only this can establish the viability of the infant and the cause and manner of death in such cases. In this paper, a gruesome killing of an infant with congenital anomalies viz. polydactyly, bilateral cleft lip and palate and low set ears, is presented. The infant was killed by an act of commission using a sharp cutting weapon, and the motive behind the crime in all possibility was to get rid of a malformed child by the parents. In the present world, modern medical science can do wonders and there is possibility of a child with congenital anomalies growing up as a normal human being. The present case emphasizes the importance of spread of awareness to the general public, especially those in remote areas, so that such primitive and gruesome crimes are not committed in the future.